Who has power? An investigation of how one teacher led her class towards understanding an academic concept through talking and microblogging. (February 2021) - Rødnes, Kari Anne; Rasmussen, Ingvill; Omland, Maren; Cook, Victoria
Abstract: This study examines work with an academic concept in a multicultural classroom where a microblogging tool was used to facilitate dialogues. The analysis of extracts from classroom talk shows how one teacher prompted students to explain, elaborate and compare their written blog posts. The verbal richness and multiple perspectives evoked through the combination of dialogue and technology allowed the students to engage in active exploration of the concept of power in a social science lesson. This paper contributes to our understanding of dialogic practice as well as how specific features of technology can facilitate productive classroom interactions. Highlights: The study investigates how a diverse class explored an academic concept. The class' work combined talk in groups and whole class with microblogging. The teacher's dialogic stance promoted shared responsibility for reasoning. Activity shifts and varied language use supported extensive student participation. Microblogging combined with dialogic teaching supported coherence across group and class talk.